A Revisit to Etiopathogenesis and Therapeutic Strategies in Alzheimer’s Disease - Kumar, Manish; Bansal, Nitin (Current Drug Targets, 2022)
Dementia is a cluster of brain abnormalities that trigger progressive memory deficits and other cognitive abilities such as skills, language, or executive function. Alzheimer’s disease (AD) is the foremost type of age-associated dementia that involves progressive neurodegeneration accompanied by profound cognitive deficits in advanced stages that severely hamper social or occupational abilities with or without the involvement of any other psychiatric condition. The last two decades witnessed a sharp increase ( 123%) in mortality due to AD type dementia, typically owing to a very low disclosure rate ( 45%) and hence, the prophylactic, as well as the therapeutic cure of AD, has been a huge challenge. Although understanding of AD pathogenesis has witnessed a remarkable growth (e.g., tauopathy, oxidative stress, lipid transport, glucose uptake, apoptosis, synaptic dysfunction, inflammation, and immune system), still a dearth of an effective therapeutic agent in the management of AD prompts the quest for newer pharmacological targets in the purview of its growing epidemiological status. Most of the current therapeutic strategies focus on modulation of a single target, e.g., inhibition of acetylcholinesterase, glutamate excitotoxicity (memantine), or nootropics (piracetam), even though AD is a multifaceted neurological disorder. There is an impedance urgency to find not only symptomatic but effective disease-modifying therapies. The present review focuses on the risk / protective factors and pathogenic mechanisms involved in AD. In addition to the existing symptomatic therapeutic approach, a diverse array of possible targets linked to pathogenic cascades have been re-investigated to envisage the pharmacotherapeutic strategies in AD.
Keywords: neuropathogenesis